Vorerfahrungen, Einstellungen und motivationale Orientierungen als mögliche Einflussfaktoren auf den Einsatz digitaler Werkzeuge im naturwissenschaftlichen Unterricht - Vogelsang, Christoph; Finger, Alexander; Laumann, Daniel; Thyssen, Christoph (Zeitschrift für Didaktik der Naturwissenschaften)

Entwicklung von Professionswissen und Unterrichtsperformanz im Lehramtsstudium Physik. Analysen zu valider Testwertinterpretation - Vogelsang, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Kulgemeyer, Christoph; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan (Zeitschrift für Pädagogik)
Angehende Physiklehrkräfte sollen im Rahmen ihres Studiums fachliches und fachdidaktisches Wissen erwerben, welches die Gestaltung lernförderlichen Unterrichts ermöglicht. Es ist allerdings empirisch nur wenig geklärt, wie sich dieses Wissen im Laufe des Studiums entwickelt und ob es zur Ausbildung von Handlungsfähigkeiten beiträgt. Um derartige Wirkungsaussagen treffen zu können, müssen Instrumente entwickelt werden, die eine valide Testwertinterpretation zulassen. In diesem Beitrag werden auf Basis von im Projekt Profile-P+ entwickelten Instrumenten Validitätsanalysen zur längsschnittlichen Entwicklung des Professionswissens von Physiklehramtsstudierenden im Verlauf des Bachelorstudiums und ihrer Fähigkeiten zur Planung und Reflexion von Physikunterricht sowie zum Erklären von physikalischen Sachverhalten vor und nach dem Praxissemester dargestellt. Neben Wissenstests kamen standardisierte Performanztests zum Einsatz. Die vorliegenden Ergebnisse sprechen dafür, dass die erhobenen Messwerte im Sinne von Wirkungsaussagen interpretiert werden können. (DIPF/Orig.)

Performance-Oriented Testing and Training in Teacher Education - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Reinhold, Peter; Schecker, Horst; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Schröder, Jan

Reflexionskompetenz trainieren: Unterrichtsvideographie als Werkzeug zur fachdidaktischen Begleitung im Praxissemester - Vogelsang, Christoph (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)

Den Einsatz digitaler Medien im naturwissenschaftlichen Unterricht lehren - Untersuchung der Lehrinitiative Didaktik:digital im Spannungsfeld von standortübergreifender Wirkungsanalyse und standortspezifischer Evaluation - Vogelsang, Christoph (Hochschuldidaktik erforscht Qualität - Profilbildung und Wertefragen in der Hochschulentwicklung III)

Integrated transition edge sensors on titanium in-diffused lithium niobate waveguides - Höpker, Jan Philipp; Gerrits, Thomas; Lita, Adriana; Krapick, Stephan; Herrmann, Harald; Ricken, Raimund; Quiring, Viktor; Mirin, Richard; Nam, Sae Woo; Silberhorn, Christine; Bartley, Tim (APL Photonics)

Durchgängige Sprachbildung und Inklusion in der sachunterrichtsdidaktischen Lehrer*innenbildung. Eine interdisziplinäre Evaluationsstudie mit Sachunterrichtsstudierenden - Blumberg, Eva; Niederhaus, Constanze; Albers, Timm; Havkic, Amra (Inklusion im Sachunterricht)

Herstellung von Wellenleitern aus Materialien der KTP-Familie - Padberg, Laura; Eigner, Christof; Santandrea, Matteo; Silberhorn, Christine

Kooperatives Arbeiten von Studierenden des Lehramts an Grund- und Förderschulen als Vorbereitung auf den inklusiven Unterricht in der Grundschule. Posterpräsentation auf der 54. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik und Bildungsforschung – Fremde Schwestern?“ - Schulze, Jan Roland; Hoya, Fabian Karl; Löper, Marwin Felix; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Effects of Interprofessional Collaboration in Inclusive Education of Pre-Service Primary School Teachers and Special Education Teachers on their Self-Concepts. Poster Presentation. ECER 2019 (European Conference on Educational Research). “Education in an Era of Risk – the Role of Educational Research for the Future“ - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Kooperativ Lernumgebungen für den inklusiven naturwissenschaftlichen Sachunterricht der Grundschule gestalten – ein Forschungs- und Entwicklungsprojekt zur Förderung von Grund- und Förderschullehrkräften (KLinG). Posterpräsentation auf der 28. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts e. V. (GDSU) - Mester, Theresa; Blumberg, Eva; Kirsch, Alexander; Hellmich, Frank; Schulze, Jan Roland; Hoya, Fabian Karl; Löper, Marwin Felix; Schwab, Susanne

Preparing Pre-service Teachers’ Team-Teaching Processes in Inclusive Science Education in Primary Schools. Poster Presentation. Porto International Conference on Research in Education (ICRE) - Löper, Marwin Felix; Hoya, Fabian Karl; Schulze, Jan Roland; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Curved Polar Dibenzocoronene Esters and Imides versus Their Planar Centrosymmetric Homologs: Photophysical and Optoelectronic Analysis - Vollbrecht, Joachim; Wiebeler, Christian; Bock, Harald; Schumacher, Stefan; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry C)

Externally Controlled Lotka-Volterra Dynamics in a Linearly Polarized Polariton Fluid - Pukrop, Matthias; Schumacher, Stefan (arXiv:1903.12534)
Spontaneous formation of transverse patterns is ubiquitous in nonlinear dynamical systems of all kinds. An aspect of particular interest is the active control of such patterns. In nonlinear optical systems this can be used for all-optical switching with transistor-like performance, for example realized with polaritons in a planar quantum-well semiconductor microcavity. Here we focus on a specific configuration which takes advantage of the intricate polarization dependencies in the interacting optically driven polariton system. Besides detailed numerical simulations of the coupled light-field exciton dynamics, in the present paper we focus on the derivation of a simplified population competition model giving detailed insight into the underlying mechanisms from a nonlinear dynamical systems perspective. We show that such a model takes the form of a generalized Lotka-Volterra system for two competing populations explicitly including a source term that enables external control. We present a comprehensive analysis both of the existence and stability of stationary states in the parameter space spanned by spatial anisotropy and external control strength. We also construct phase boundaries in non-trivial regions and characterize emerging bifurcations. The population competition model reproduces all key features of the switching observed in full numerical simulations of the rather complex semiconductor system and at the same time is simple enough for a fully analytical understanding of the system dynamics.

Preparing Pre-service Teachers’ Team-Teaching Processes in Inclusive Science Education in Primary Schools. Poster Presentation. Porto International Conference on Research in Education (ICRE) - Löper, Marwin Felix; Hoya, Fabian Karl; Schulze, Jan Roland; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne

Pre-service Primary School Teachers’ Preparation for Team-Teaching in Inclusive Schools. Poster Presentation. 18th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2019. „Thinking Tomorrows’s Education: Learning from the past, in the present and for the future" - Hoya, Fabian Karl; Löper, Marwin Felix; Schulze, Jan Roland; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Molecular Doping of PCPDT-BT Copolymers: Comparison of Molecular Complexes with and Without Integer Charge Transfer - Dong, Chuan-Ding; Schumacher, Stefan
Molecular doping in conjugated polymers is a crucial process for their application in organic photovoltaics and optoelectronics. In the present work we theoretically investigate p-type molecu- lar doping in a series of (poly[2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b”]dithiophene)-alt- 4,7-(2,1,3-benzothiadiazole)] (PCPDT-BT) conjugated oligomers with different lengths and three widely-used dopants with different electron affinities, namely F4TCNQ, F6TCNNQ, and CN6-CP. We study in detail the molecular geometry of possible oligomer-dopant complexes and its influence on the doping mechanisms and electronic system properties. We find that the mechanisms of dop- ing and charge transfer observed sensitively depend on the specific geometry of the oligomer-dopant complexes. For a given complex different geometries may exist, some of which show transfer of an entire electron from the oligomer chain onto the dopant molecule resulting in an integer-charge transfer complex, leaving the system in a ground state with broken spin symmetry. In other ge- ometries merely hybridization of oligomer and dopant frontier orbitals occurs with partial charge transfer but spin-symmetric ground state. Considering the resulting electronic density of states both cases may well contribute to an increased electrical conductivity of corresponding film samples while the underlying physical mechanisms are entirely different.

Wie können Studierende des Lehramts an Grund- und Förderschulen auf das kooperative Arbeiten in der inklusiven Grundschule vorbereitet werden? Posterpräsentation auf der 7. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Schulze, Jan Roland; Hoya, Fabian Karl; Löper, Marwin Felix; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Entwicklung kooperativen Arbeitens bei Lehramtsstudierenden für den naturwissenschaftlichen Sachunterricht in der inklusiven Grundschule. Posterpräsentation auf dem 8. Paderborner Grundschultag - Löper, Marwin Felix; Görel, Gamze; Hoya, Fabian Karl; Kirsch, Alexander; Mester, Theresa; Schulze, Jan Roland; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Controllable high-speed polariton waves in a PT-symmetric lattice - Ma, Xuekai; Kartashov, Yaroslav Y; Gao, Tingge; Schumacher, Stefan (New Journal of Physics)

Efficient C-band single-photon upconversion with chip-scale Ti-indiffused pp-LiNbO3 waveguides - Xie, Zhenda; Luo, Kai Hong; Chang, Kai Chi; Panoiu, Nicolae C.; Herrmann, Harald; Silberhorn, Christine; Wong, Chee Wei (Applied Optics)
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Estimating the Indistinguishability of Heralded Single Photons Using Second-Order Correlation - Faruque, Imad I.; Sinclair, Gary F.; Bonneau, Damien; Ono, Takafumi; Silberhorn, Christine; Thompson, Mark G.; Rarity, John G. (Physical Review Applied)
Keywords: General Physics and Astronomy

Temporally multimode four-photon Hong-Ou-Mandel interference - Ferreri, Alessandro; Ansari, V.; Silberhorn, Christine; Sharapova, Polina R. (Physical Review A)

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Quasiparticle and excitonic effects in the optical response of KNbO3 - Schmidt, Falko; Riefer, Arthur; Schmidt, Wolf Gero; Schindlmayr, Arno; Imlau, Mirco; Dobener, Florian; Mengel, Nils; Chatterjee, Sangam; Sanna, Simone (Physical Review Materials)
The cubic, tetragonal, and orthorhombic phase of potassium niobate (KNbO3) are studied based on density-functional theory. Starting from the relaxed atomic geometries, we analyze the influence of self-energy corrections on the electronic band structure within the GW approximation. We find that quasiparticle shifts widen the direct (indirect) band gap by 1.21 (1.44), 1.58 (1.55), and 1.67 (1.64) eV for the cubic, tetragonal, and orthorhombic phase, respectively. By solving the Bethe-Salpeter equation, we obtain the linear dielectric function with excitonic and local-field effects, which turn out to be essential for good agreement with experimental data. From our results, we extract an exciton binding energy of 0.6, 0.5, and 0.5 eV for the cubic, tetragonal, and orthorhombic phase, respectively. Furthermore, we investigate the nonlinear second-harmonic generation (SHG) both theoretically and experimentally. The frequency-dependent second-order polarization tensor of orthorhombic KNbO3 is measured for incoming photon energies between 1.2 and 1.6 eV. In addition, calculations within the independent-(quasi)particle approximation are performed for the tetragonal and orthorhombic phase. The novel experimental data are in excellent agreement with the quasiparticle calculations and resolve persistent discrepancies between earlier experimental measurements and ab initio results reported in the literature.

Excited-state band mapping and momentum-resolved ultrafast population dynamics in In/Si(111) nanowires investigated with XUV-based time- and angle-resolved photoemission spectroscopy - Nicholson, C. W.; Puppin, M.; Lücke, A.; Gerstmann, Uwe; Krenz, Marvin; Schmidt, Wolf Gero; Rettig, L.; Ernstorfer, R.; Wolf, M. (Physical Review B)

Water Splitting Reaction at Polar Lithium Niobate Surfaces - Dues, Christof; Schmidt, Wolf Gero; Sanna, Simone (ACS Omega)

Mode-independent quantum entanglement for light - Sperling, Jan; Perez-Leija, Armando; Busch, Kurt; Silberhorn, Christine (Physical Review A)

Nonlinear integrated quantum electro-optic circuits - Luo, Kai-Hong; Brauner, Sebastian; Eigner, Christof; Sharapova, Polina; Ricken, Raimund; Meier, Torsten; Herrmann, Harald; Silberhorn, Christine (Science Advances)
An integrated chip with quantum state generation, active polarization manipulation, and precise time control is demonstrated.
Keywords: Multidisciplinary

Intensity-dependent degenerate and non-degenerate nonlinear optical absorption of direct-gap semiconductors - Hannes, Wolf-Rüdiger; Krauß-Kodytek, Laura; Ruppert, Claudia; Betz, Markus; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXIII)

Higher-order contributions and nonperturbative effects in the nondegenerate nonlinear optical absorption of semiconductors using a two-band model - Hannes, Wolf-Rüdiger; Meier, Torsten (Physical Review B)

Potassium titanyl phosphate (KTP) quasiparticle energies and optical response - Neufeld, Sergej; Bocchini, Adriana; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Journal of Physics: Materials)
The KTiOPO4 (KTP) band structure and dielectric function are calculated on various levels of theory starting from density-functional calculations. Within the independent-particle approximation an electronic transport gap of 2.97 eV is obtained that widens to about 5.23 eV when quasiparticle effects are included using the GW approximation. The optical response is shown to be strongly anisotropic due to (i) the slight asymmetry of the TiO6 octahedra in the (001) plane and (ii) their anisotropic distribution along the [001] and [100] directions. In addition, excitonic effects are very important: The solution of the Bethe–Salpeter equation indicates exciton binding energies of the order of 1.5 eV. Calculations that include both quasiparticle and excitonic effects are in good agreement with the measured reflectivity.

Experimental Reconstruction of Entanglement Quasiprobabilities - Sperling, Jan; Meyer-Scott, E.; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physical Review Letters)

Subcycle Wannier-Stark Localization by Mid-Infrared Bias in Gallium Arsenide - Meier, Torsten; Bühler, Johannes; Schmidt, Christian; Heinrich, Alexander-Cornelius; Allerbeck, Jonas; Podzimski, Reinold; Berghoff, Daniel; Schmidt, Wolf Gero; Reichl, Christian; Wegscheider, Werner; Brida, Daniele; Leitenstorfer, Alfred (XXI International Conference on Ultrafast Phenomena 2018 (UP 2018))
The fundamental interband absorption in gallium arsenide shows a strong blue shift when biased by mid-infrared transients exceeding 10 MV/cm. This subcycle feature is induced by the localization of electronic wavefunctions from 3D to 2D.

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Generating two-mode squeezing with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten (arXiv:1912.09097)
Measurement-induced nonclassical effects in a two-mode interferometer are investigated theoretically using numerical simulations and analytical results. We demonstrate that for certain parameters measurements within the interferometer lead to the occurrence of two-mode squeezing. The results strongly depend on the detection probability, the phase inside the interferometer, and the choice of the input states. The appropriate parameters for maximized squeezing are obtained. We analyze the influence of losses and confirm that the predicted effects are within reach of current experimental techniques.

Attosecond temporal confinement of interband excitation by intraband motion - Song, Xiaohong; Zuo, Ruixin; Yang, Shidong; Li, Pengcheng; Meier, Torsten; Yang, Weifeng (Optics Express)

Ballistic photocurrents in semiconductor quantum wells caused by the excitation of asymmetric excitons - Duc, Huynh Thanh; Ngo, Cong; Meier, Torsten (Physical Review B)

Oxygen and potassium vacancies in KTP calculated from first principles - Bocchini, Adriana; Neufeld, Sergej; Gerstmann, Uwe; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Bloch oscillations of multidimensional dark soliton wave packets and light bullets - Driben, R; Ma, Xuekai; Schumacher, Stefan; Meier, Torsten (Optics Letters)

Entwicklung von Professionswissen und Unterrichtsperformanz im Lehramtsstudium Physik. Analysen zu valider Testwertinterpretation - Vogelsang, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Kulgemeyer, Christoph; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan (Zeitschrift für Pädagogik)
Angehende Physiklehrkräfte sollen im Rahmen ihres Studiums fachliches und fachdidaktisches Wissen erwerben, welches die Gestaltung lernförderlichen Unterrichts ermöglicht. Es ist allerdings empirisch nur wenig geklärt, wie sich dieses Wissen im Laufe des Studiums entwickelt und ob es zur Ausbildung von Handlungsfähigkeiten beiträgt. Um derartige Wirkungsaussagen treffen zu können, müssen Instrumente entwickelt werden, die eine valide Testwertinterpretation zulassen. In diesem Beitrag werden auf Basis von im Projekt Profile-P+ entwickelten Instrumenten Validitätsanalysen zur längsschnittlichen Entwicklung des Professionswissens von Physiklehramtsstudierenden im Verlauf des Bachelorstudiums und ihrer Fähigkeiten zur Planung und Reflexion von Physikunterricht sowie zum Erklären von physikalischen Sachverhalten vor und nach dem Praxissemester dargestellt. Neben Wissenstests kamen standardisierte Performanztests zum Einsatz. Die vorliegenden Ergebnisse sprechen dafür, dass die erhobenen Messwerte im Sinne von Wirkungsaussagen interpretiert werden können. (DIPF/Orig.)

Beschleuniger-Experimente mit sichtbarer Spur der Elektronen - Eine Unterrichtsreihe in der Teilchenphysik - Bechstein, Stefan; Stahl, Achim; Riese, Josef (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Kiel 2018)

Profile-P+: Kompetenz und Performanz im Lehramtsstudium Physik - Vogelsang, Christoph; Riese, Josef; Borowski, Andreas; Kulgemeyer, Christoph (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Kiel 2018)

Erfassung der Fähigkeit zur Unterrichtsplanung im Physikunterricht - Schröder, Jan; Vogelsang, Christoph; Riese, Josef (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Kiel 2018)

Konzeption eines Lernzirkels zu experimentellen Kompetenzen - Goertz, Simon; Klein, Patrick; Riese, Josef; Heinke, Heidrun (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Kiel 2018)

Die Veränderung physikdidaktischen Wissens im Lehr-Lern-Seminar - Joswig, Ann-Kathrin; Riese, Josef (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Kiel 2018)

Performance-Oriented Testing and Training in Teacher Education - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Reinhold, Peter; Schecker, Horst; Buschütter, David; Enkrott, Patrick; Kempin, Maren; Schröder, Jan (Student Learning Outcomes Assessment in Higher Education – Perspectives, Concepts and Approaches for Research, Transfer and Implementation (KoKoHs Working Papers, 12))

Development of Prospective Physics Teachers’ Pedagogical Content Knowledge While preparing for an Internship - Joswig-Käfer, Ann-Kathrin; Riese, Josef (E-Book Proceedings of the ESERA 2019 Conference: The beauty and pleasure of understanding: engaging with contemporary challenges through science education)

Assessing Student Teachers‘ Skills to plan Physics Lessons - Schröder, Jan; Vogelsang, Christoph; Riese, Josef (E-Book Proceedings of the ESERA 2019 Conference: The beauty and pleasure of understanding: engaging with contemporary challenges through science education)

Didaktische Rekonstruktion der Beschleunigerphysik und Entwicklung eines Lehr-Linearbeschleunigers - Bechstein, Stefan; Stahl, Achim; Riese, Josef (PhyDid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung 2019 in Aachen)

Veränderung des physikdidaktischen Wissens im Verlauf eines Lehr-Lern-Seminars - Joswig, Ann-Kathrin; Riese, Josef (PhyDid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung 2019 in Aachen)

Professionswissen von Physiklehramtsstudierenden in Österreich - Krumphals, Ingrid; Riese, Josef (Forschungsperspektiven 11: Lehrerinnen und Lehrerbildung in der Sekundarstufe)

Molecular Beam Epitaxy Growth and Characterization of Germanium‐Doped Cubic Al x Ga 1− x N - Deppe, Michael; Henksmeier, Tobias; Gerlach, Jürgen W.; Reuter, Dirk; As, Donat J. (physica status solidi (b))

Kompetenzorientierte, universitäre Laborpraktika - Das Paderborner Physik Praktikum (3P) - Bauer, Anna; Sacher, Marc (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung)

Operationalisierung der experimentellen Kompetenz (Physik)Studierender - Bauer, Anna; Reinhold, Peter; Sacher, Marc (Qualitätsvoller Chemie- und Physikunterricht – normative und empirische Dimensionen)

On the Adsorption of DNA Origami Nanostructures in Nanohole Arrays - Brassat, Katharina; Ramakrishnan, Saminathan; Bürger, Julius; Hanke, Marcel; Doostdar, Mahnaz; Lindner, Jörg; Grundmeier, Guido; Keller, Adrian (Langmuir)
DNA origami nanostructures are versatile substrates for the controlled arrangement of molecular capture sites with nanometer precision and thus have many promising applications in singlemolecule bioanalysis. Here, we investigate the adsorption of DNA origami nanostructures in nanohole arrays which represent an important class of biosensors and may benefit from the incorporation of DNA origami-based molecular probes. Nanoholes with well-defined diameter that enable the adsorption of single DNA origami triangles are fabricated in Au films on Siwafers by nanosphere lithography. The efficiency of directed DNA origami adsorption on the exposed SiO2 areas at the bottoms of the nanoholes is evaluated in dependence of various parameters, i.e., Mg2+ and DNA origami concentrations, buffer strength, adsorption time, and nanohole diameter. We observe that the buffer strength has a surprisingly strong effect on DNA origami adsorption in the nanoholes and that multiple DNA origami triangles with 120 nm edge length can adsorb in nanoholes as small as 120 nm in diameter. We attribute the latter observation to the low lateral mobility of once adsorbed DNA origami on the SiO2 surface, in combination with parasitic adsorption to the Au film. While parasitic adsorption can be suppressed by modifying the Au film with a hydrophobic self-assembled monolayer, the limited surface mobility of the adsorbed DNA origami still leads to poor localization accuracy in the nanoholes and results in many DNA origami crossing the boundary to the Au film even under optimized conditions. We discuss possible ways to minimize this effect by varying the composition of the adsorption buffer, employing different fabrication conditions, or using other substrate materials for nanohole array fabrication.

Tomography and Purification of the Temporal-Mode Structure of Quantum Light - Ansari, Vahid; Donohue, John M.; Allgaier, Markus; Sansoni, Linda; Brecht, Benjamin; Roslund, Jonathan; Treps, Nicolas; Harder, Georg; Silberhorn, Christine (Physical Review Letters)

Tailoring nonlinear processes for quantum optics with pulsed temporal-mode encodings - Ansari, Vahid; Donohue, John M.; Brecht, Benjamin; Silberhorn, Christine (Optica)

Metasurface holography: from fundamentals to applications - Huang, Lingling; Zhang, Shuang; Zentgraf, Thomas (Nanophotonics)

Exact formulation of the transverse dynamic spin susceptibility as an initial-value problem - Schindlmayr, Arno (Advances in Mathematical Physics)
The transverse dynamic spin susceptibility is a correlation function that yields exact information about spin excitations in systems with a collinear magnetic ground state, including collective spin-wave modes. In an ab initio context, it may be calculated within many-body perturbation theory or time-dependent density-functional theory, but the quantitative accuracy is currently limited by the available functionals for exchange and correlation in dynamically evolving systems. To circumvent this limitation, the spin susceptibility is here alternatively formulated as the solution of an initial-value problem. In this way, the challenge of accurately describing exchange and correlation in many-electron systems is shifted to the stationary initial state, which is much better understood. The proposed scheme further requires the choice of an auxiliary basis set, which determines the speed of convergence but always allows systematic convergence in practical implementations.

On the Adsorption of DNA Origami Nanostructures in Nanohole Arrays - Brassat, Katharina; Ramakrishnan, Saminathan; Bürger, Julius; Hanke, Marcel; Doostdar, Mahnaz; Lindner, Jörg; Grundmeier, Guido; Keller, Adrian (Langmuir)

Multichannel vectorial holographic display and encryption - Zhao, Ruizhe; Sain, Basudeb; Wei, Qunshuo; Tang, Chengchun; Li, Xiaowei; Weiss, Thomas; Huang, Lingling; Wang, Yongtian; Zentgraf, Thomas (Light: Science & Applications)

Photonic crystal properties of Si and SiO2 nanopillar arrays fabricated by nanosphere lithography and metal-assisted wet-chemical etching - Kismann, Michael; Riedl, Thomas; Wu, Xia; Wagner, Thorsten; Lindner, Jörg

Strain Relaxation in InAs Nanoislands on top of GaAs (111) A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Reuter, Dirk; Lindner, Jörg

MBE Growth of InAs on Nanopillar-Patterned GaAs (111) A - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Reuter, Dirk; Lindner, Jörg

Impact of shell growth on recombination dynamics and exciton-phonon interaction in CdSe-CdS core-shell nanoplatelets - Achtstein, Alexander W.; Marquardt, Oliver; Scott, Riccardo; Ibrahim, Mohamed; Riedl, Thomas; Prudnikau, Anatol V.; Antanovich, Artsiom; Owschimikow, Nina; Lindner, Jörg; Artemyev, Mikhail; Woggon, Ulrike (accepted 05.09.2018)

Self-assembled Surface Patterns for Controlled Nanoparticle Placement and Improved Semiconductor Heteroepitaxy - Brassat, Katharina; Riedl, Thomas; Lindner, Jörg

Exciton-Phonon Interaction in Core-Only, Core-Shell Nanoplatelets and Quantum Dots - Scott, Riccardo; Prudnikau, Anatol; Antanovich, Artsiom; Christodoulou, Soririos; Riedl, Thomas; Bertrand, Guilaume; Owschimikow, Nina; Lindner, Jörg; Hens, Zeger; Moreels, Iwan; Artemyev, Mikhail; Woggon, Ulrike; et al. (submitted to Nano Letters)

Stability of Heteroepitaxial Coherent Growth Modes on Nanowire Radial Surfaces - Riedl, Thomas; Lindner, Jörg (submitted to Phys. Rev. Mat.)

Modification of block copolymer lithography masks by O2 plasma treatment: Insights from lift off experiments, nanopore etching and free membranes - Brassat, Katharina; Kool, Daniel; Lindner, Jörg (To be submitted)

Nanostructure Research using Transmission Electron Microscopy at the new OWL Analytic Centre - Riedl, Thomas; Bürger, Julius; Kunnathully, Vinay; Wiegand, Marie; Duschik, K.; Ramermann, D.; Ennen, I.; Hertle, Y.; Schaper, Mirko; Hellweg, T.; Hütten, A.; Lindner, Jörg

State-of-the-art transmission electron microscopy in the imaging and scanning mode - Lindner, Jörg

Decay and revival of electron spin polarization in an ensemble of (In,Ga)As quantum dots - Evers, E.; Belykh, V. V.; Kopteva, N. E.; Yugova, I. A.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Interlayer charge transfer in n-modulation doped Al1−x Ga x As–GaAs single heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Basic Requirements of Spin-Flip Raman Scattering on Excitonic Resonances and Its Modulation through Additional High-Energy Illumination in Semiconductor Heterostructures - Debus, J.; Kudlacik, D.; Sapega, V. F.; Shamirzaev, T. S.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Waag, A.; Bayer, M. (Physics of the Solid State)

Formation of self-assembled GaAs quantum dots via droplet epitaxy on misoriented GaAs(111)B substrates - Trapp, Alexander; Reuter, Dirk (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics: Materials, Processing, Measurement, and Phenomena)

Site-controlled droplet epitaxy of GaAs quantum dots by deposition through shadow masks - Zolatanosha, Viktoryia; Reuter, Dirk (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics: Materials, Processing, Measurement, and Phenomena)

Spin inertia of resident and photoexcited carriers in singly charged quantum dots - Zhukov, E. A.; Kirstein, E.; Smirnov, D. S.; Yakovlev, D. R.; Glazov, M. M.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Greilich, A. (Physical Review B)

Optical Properties of Cubic GaN Quantum Dots Grown by Molecular Beam Epitaxy - Blumenthal, Sarah; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Nonlinear Quasi-Phase Matching with metasurfaces - Heron, S.; Reineke, B.; Vezian, S.; Zentgraf, Thomas; Damilano, B.; Genevet, P. (2018 12th International Congress on Artificial Materials for Novel Wave Phenomena (Metamaterials))

Near-field plasmonic beam engineering by complex amplitude modulation based on metasurface (Conference Presentation) - Sun, Lin; Zhang, Xiaomeng; Zhao, Ruizhe; Li, Xiaowei; Wang, Jia; Bai, Benfeng; Wang, Yongtian; Zentgraf, Thomas; Huang, Lingling; Song, Xu (Nanophotonics VII)

Engineering integrated sources of entangled photon pairs - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Harder, Georg; Sansoni, Linda; Herrmann, Harald; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; Barkhofen, Sonja; et al. (Frontiers in Optics / Laser Science)

Engineering integrated sources of entangled photon pairs - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Harder, Georg; Sansoni, Linda; Herrmann, Harald; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Bartley, Tim J.; Barkhofen, Sonja; et al. (Frontiers in Optics / Laser Science)

Incomplete Detection of Nonclassical Phase-Space Distributions - Bohmann, M.; Tiedau, J.; Bartley, Tim; Sperling, J.; Silberhorn, C.; Vogel, W. (Physical Review Letters)

Hierarchical nanopores formed by block copolymer lithography on the surfaces of different materials pre-patterned by nanosphere lithography - Brassat, Katharina; Kool, Daniel; Bürger, Julius; Lindner, Jörg (Nanoscale)
Bottom-up patterning techniques allow for the creation of surfaces with ordered arrays of nanoscale features on large areas. Two bottom-up techniques suitable for the formation of regular nanopatterns on different length scales are nanosphere lithography (NSL) and block copolymer (BCP) lithography. In this paper it is shown that NSL and BCP lithography can be combined to easily design hierarchically nanopatterned surfaces of different materials. Nanosphere lithography is used for the pre-patterning of surfaces with antidots, i.e. hexagonally arranged cylindrical holes in thin films of Au, Pt and TiO2 on SiO2, providing a periodic chemical and topographical contrast on the surface suitable for templating in subsequent BCP lithography. PS-b-PMMA BCP is used in the second self-assembly step to form hexagonally arranged nanopores with sub-20 nm diameter within the antidots upon microphase separation. To achieve this the microphase separation of BCP on planar surfaces is studied, too, and it is demonstrated for the first time that vertical BCP nanopores can be formed on TiO2, Au and Pt films without using any neutralization layers. To explain this the influence of surface energy, polarity and roughness on the microphase separation is investigated and discussed along with the wetting state of BCP on NSL-pre-patterned surfaces. The presented novel route for the creation of advanced hierarchical nanopatterns is easily applicable on large-area surfaces of different materials. This flexibility makes it suitable for a broad range of applications, from the morphological design of biocompatible surfaces for life science to complex pre-patterns for nanoparticle placement in semiconductor technology.

A Novel Lubricant Based on Covalent Functionalized Graphene Oxide Quantum Dots - Wolk, Andreas; Rosenthal, Marta; Neuhaus, Stephan; Huber, Klaus; Brassat, Katharina; Lindner, Jörg; Grothe, Richard; Grundmeier, Guido; Bremser, Wolfgang; Wilhelm, René (Scientific Reports)
Dodecyl amine edge functionalized few-layer graphene oxide quantum dots were synthesized in good yields. The covalent functionalization was demonstrated with NMR and AFM-IR. The resulting structure and particle size was measured with AFM and HRTEM. The thermal stability of the compound was investigated and showed a stability of up to 220 °C. The modified graphene oxide quantum dots showed excellent solubility in various organic solvents, including ethers, methanol, toluene, n-hexane, heptane, xylene, dichloromethane and toluene. The stability of a resulting toluene solution was also proven by static light scattering measurements over several days. The excellent solubility gives the possibility of an efficient and fast spray application of the functionalized graphene oxide quantum dots to steel surfaces. Hence, the macroscopic friction behavior was investigated with a Thwing-Albert FP-2250 friction tester. A thin film of the dodecyl amine functionalized graphene oxide quantum dots on steel lowered the friction coefficient from 0.17 to 0.11 and revealed a significant corrosion inhibition effect.

Easily Accessible Protein Nanostructures via Enzyme Mediated Addressing - Rüdiger, Arne A.; Brassat, Katharina; Lindner, Jörg; Bremser, Wolfgang; Strube, Oliver I. (Langmuir)
Site-specific formation of nanoscaled protein structures is a challenging task. Most known structuring methods are either complex and hardly upscalable or do not apply to biological matter at all. The presented combination of enzyme mediated autodeposition and nanosphere lithography provides an easy-to-apply approach for the buildup of protein nanostructures over a large scale. The key factor is the tethering of enzyme to the support in designated areas. Those areas are provided via prepatterning of enzymatically active antidots with variable diameters. Enzymatically triggered protein addressing occurs exclusively at the intended areas and continues until the entire active area is coated. After this, the reaction self-terminates. The major advantage of the presented method lies in its easy applicability and upscalability. Large area structuring of entire support surfaces with features on the nanometer scale is performed efficiently and without the necessity of harsh conditions. These are valuable premises for large-scale applications with potentials in biosensor technology, nanoelectronics, and life sciences.

With directed self-arrangement of DNA origami to large-area quantum dot arrays - Grundmeier, Guido; Brassat, Katharina; Keller, A.; Lindner, Jörg

Hierarchical nanopore and nanoring arrays by self-assembly techniques - Brassat, Katharina; Kool, Daniel; Lindner, Jörg

Ti-6Al-4V alloy: 3D printing of lightweight implants and nanopatterning by self-assembly - Brassat, Katharina; Taube, A.; Kool, Daniel; Tasche, L.; Hoyer, K.P.; Schaper, Mirko; Lindner, Jörg

Morphology investigation of nanopores by block copolymer lithography on different material surfaces - Brassat, Katharina; Kool, Daniel; Taube, A.; Schaper, Mirko; Lindner, Jörg

Nanoscopic protein arrays on BCP prepatterned surfaces - Brassat, Katharina; Brüngeler, A.; Bremser, W.; Strube, O.I.; Lindner, Jörg

Hierarchical nanopatterns by site-selective DNA origami adsoprtion on pre-patterned surfaces - Brassat, Katharina; Ramakrishna, S.; Keller, A.; Lindner, Jörg

Simulation of Transport Processes during the Convective Self-Assembly of Colloidal Nanomasks - Drude, Dennis; Lindner, Jörg

Protein and DNA origami arrays on large areas by directed self-assembly - Brassat, Katharina; Bremser, W.; Strube, O.; Grundmeier, G.; Keller, A.; Lindner, Jörg

Selbstorganisation für die Nanotechnik von morgen - Lindner, Jörg

Nanoscale materials and interface design by self-organization - Lindner, Jörg

Third Harmonic Generation Enhanced by Multipolar Interference in Complementary Silicon Metasurfaces - Chen, Shumei; Rahmani, Mohsen; Li, King Fai; Miroshnichenko, Andrey; Zentgraf, Thomas; Li, Guixin; Neshev, Dragomir; Zhang, Shuang (ACS Photonics)

Spin and Geometric Phase Control Four-Wave Mixing from Metasurfaces - Li, Guixin; Sartorello, Giovanni; Chen, Shumei; Nicholls, Luke H.; Li, King Fai; Zentgraf, Thomas; Zhang, Shuang; Zayats, Anatoly V. (Laser & Photonics Reviews)

Editorial for the theories and applications of metasurfaces - Guo, Zhongyi; Chen, Xianzhong; Zentgraf, Thomas (Journal of Physics D: Applied Physics)